Living opera - Jampol, Joshua (Oxford University Press, 2010)
Living Opera is a fascinating collection of 20 wide-ranging interviews with the preeminent opera professionals working on and behind the stage today. Joshua Jampol invites opera-lovers to listen in as performers such as Renee Fleming, Natalie Dessay, Rolando Villazon and Placido Domingo speak in exceptionally frank terms about their strengths and weaknesses, and address such hard-hitting, enduring topics as how they deal with critics, vocal troubles, and balancing their career and family lives. We hear conductors such as James Conlon, Esa-Pekka Salonen, and Kent Nagano discuss their likes and
Keywords: Opera : Interviews; Dramatic music : History and criticism